Community participation in building village environmental health Jatiendah Village, Cilengkrang Sub-District, Bandung - Winarti, Agus; Rizkiah, Riza; Astuti, Livia (Technium Social Sciences Journal, 2023)
Environmental health, which is part of public health, has the aim of fostering and improving the degree of health and daily life, both physical, mental, and social. Considering the village as an institution that is in direct contact with the community and the main person in charge of implementing government, development, and society, the village government must be able to make every effort to include all development activities evenly and balanced by paying attention to all environmental health. Jatiendah Village, Cilengkrang sub-district, is one of the villages in Bandung Regency which is one of the research targets in an effort to build village environmental health. Based on the results of the research conducted, the level of community awareness and participation in efforts to build village environmental health is still not good. Through the community empowerment process, we hope to help the community to be able to actively participate in answering every social problem that occurs in the community, especially related to village environmental health.